Obesity The Medical Practitioner's Essential Guide - Blackstone, Robin P. (Springer International Publishing : Imprint: Springer, 2016)
This book is the most current, comprehensive medical text focusing specifically on obesity and its related syndromes and diseases. This text takes the newest science and latest research about obesity and renders the information imminently readable and immediately useful to the medical practitioner charged with providing best practices health care for patients who are obese. In the process, this text scientifically clarifies obesity as a disease of epidemic proportions, debunks common myths about obesity, and challenges medicine's traditional and oftentimes limited view of obesity. More specifically, in Obesity: The Medical Practitioner's Essential Guide you will find comprehensive, accurate, science-based information about the epidemiology, biology, genetics, psychology, discrimination and prejudice, causes, and effects of obesity, as well as the latest science about obesity's related syndromes and diseases. In addition, this book provides the medical practitioner with specific best practices, including preferred methods of measurement, preferred methods of obesity screening, a system of graded interventions, a comprehensive description and analysis of various bariatric/surgical interventions, and a proposed population management strategy. This medical text focusing on obesity and its related syndromes and diseases is not only an invaluable reference source for current front line practitioners, but is an essential tool that can be used both domestically and internationally to educate all students in medical schools, nursing programs, physician assistant programs, doctor of osteopath programs, medical weight loss clinics, and any other health science programs.